FOLLOW-UP IN THE FORMATION OF INDEPENDENT SKILLS EDUCATIONAL ACTIVITIES OF STUDENTS OF THE PEDAGOGICAL UNIVERSITY ORGANIZATIONAL, OPERATIONAL AND SUBJECT LEVEL - O.V. Malykhin (Academy of Cognitive and Natural Sciences, 2007)
The article deals with the problem concerning existing possibilities of pedagogical influence while forming students' self-directed educational activities skills in Pedagogical University on organizational, functional, and subjective levels.